Retrieving a Soul Part that Fractured During Trauma. (15th April 2020) - Simington, Jane; Wagner, Joan
Abstract : A post-traumatic response includes alterations in functioning on the physical, mental, emotional, social, and spiritual levels. Interest in using complementary therapies resulted from PTSD patient requests for modalities that address their spiritual needs. The positive neurophysiology effects on PTSD symptoms produced by spiritual practices generates renewed interest in the approaches to the psyche proposed by Carl Jung, and also in traditional cultural practices for healing trauma. In traditional worldviews the shock of trauma can cause a part of the soul to fracture off and remain trapped in a non-ordinary reality. Jung encouraged therapeutic regression to connect with the lost part. Regression therapy gained support following MRI studies showing that trauma narratives are replayed through the brain's right hemisphere. MRI studies support research showing that right hemisphere options, such as visualization, increase the possibility for healing trauma. The purpose of this research was to determine if there were pre- and post-intervention differences when using spiritually-focused guided visualization to regress subjects to a traumatic event, there to reclaim and reintegrate a soul part that had fractured off during trauma. Eight study participants from an Indigenous Community in Canada participated. Pre-to-post score differences on the PCL-5 suggest a positive and clinically meaningful response to the intervention. The themes derived from the narrative descriptions indicate that the soul retrieval intervention increased the well-being of the study participants.